Macrophage Immunometabolism: Where Are We (Going)? - Van den Bossche, Jan; O’Neill, Luke A.; Menon, Deepthi (Trends in immunology, 2017)
A growing number of findings highlight the crucial role of metabolic reprogramming in macrophage activation. Metabolic pathways are closely interconnected and recent literature demonstrates the need for glucose metabolism in anti-inflammatory as well as inflammatory macrophages. Moreover, fatty acid oxidation (FAO) not only supports anti-inflammatory responses as described formerly but also drives inflammasome activation in inflammatory macrophages. Hence, defining glycolysis as proinflammatory and FAO as anti-inflammatory may be an oversimplification. Here we review how the rapid growth of the immunometabolism field has improved our understanding of macrophage activation and at the same time has led to an increase in the appearance of contradictory observations. To conclude we discuss current challenges in immunometabolism and present crucial areas for future research. Metabolic reprogramming of macrophages plays a predominant role in regulating their phenotype but also their plasticity. Metabolic repurposing of mitochondria is key to the regulation of proinflammatory responses including the expression of pro-IL-1β and the generation of reactive oxygen species via reverse electron transport. In vivo macrophages are subject to a plethora of stimuli that often do not fully fit in the binary M1/M2 frame. Moreover, nutrient competition adds an extra layer of complexity to their functional regulation. The differences between human and mouse macrophages remain in the process of being elucidated. The inability of human macrophages to produce nitric oxide in vitro, unlike murine macrophages, introduces the possibility of differential metabolic reprogramming between the two cell types.